Penggunaan Triptofan dalam Pakan untuk Menurunkan Kanibalisme Ikan Kakap Putih (Lates calcarifer) - Mainisa, Mainisa; Juliana, Juliana; Khalil, Munawwar; Mahdaliana, Mahdaliana; Salamah, Salamah (Jurnal Laot Ilmu Kelautan, 2024)
White snapper (Lates calcarifer) is one of the leading marineculture commodities in Indonesia, snapper has a relatively faster growth and has high economic value. One of the factors that cause failure in snapper cultivation in Indonesia is the high level of cannibalism in fish fry. The purpose of this study was the addition of tryptophan to feed whether it affected the level of cannibalism, growth and survival of white snapper. This study used a non-factorial completely randomized design (CRD) method consisting of 4 treatments and 3 replications. The treatments used were Treatment A (control), B (Tryptophan 1%/kg feed), C (Tryptophan 1.5 %/kg feed), D (Tryptophan 2%/kg feed. The lowest cannibalism of snapper was found in treatment B (Tryptophan 1%/kg of feed) with a cannibalism rate of 35.7% and a survival rate of 56.67%.